The Angkor guidebook : your essential companion to the temples - Booth, Andrew J. ([Place of publication not identifed] : [publisher not identified], 2015)
The text reflects the latest opinions of the leading academics yet has been carefully edited to be concise and accessible to the reader. Virtual reconstructions of the ruins as they would have appeared in their heyday better enable you to interpret what remains today. Extensive collaboration between the artist and the academic community have resulted in the most accurate and wide-ranging visual reconstruction so far attempted. With this work the casual visitor can better appreciate the temples as the original designers intended they be seen. Period photographs provide a valuable insight into another chapter of the history of the monuments and a window onto work from the early years of the 20th century to stabilise and restore the sites.
Key to symbols -- Foreword by Christophe Pottier -- Preface -- History of Angkor, an introduction -- Temple architecture, decay and restoration -- Lidar developments -- A note from the artist -- Virtual reconstruction details -- Temples of Central Angkor Thom -- Temples outside Angkor Thom -- Temples further afield and lesser visited sites -- Nature spotting around the temples -- Suggested itineraries -- Glossary of terminology -- Biographies, credits and further reading -- Check list for kids (and grown-ups) -- Travel planning aand touring tips -- Chronology of the monuments -- Folding map of the Angkor archaeological park